Depresión y la influencia en el aprendizaje de un estudiante - Moyano Angulo, Helen Brigitte (2020)
This case study is mainly aimed at depression and its influence on learning, because in recent times there is a large percentage of people who have been overwhelmed by this disease. In this paper it is important to emphasize that because of its content it is immersed in the Psychology Career Research Line that covers prevention and diagnosis and as a Sub-Line of research, Behavioral Disorders and its impact on the teaching process learning. To begin in the introduction an opening is made where the whole process is detailed in a few words. The justification details the importance, contribution, beneficiaries, feasibility and feasibility of this research, in this case the student and the people around him. Further on, the objective is known, which consists in evaluating the influence of depression on learning, followed by the theoretical bases or supports where each variable is specifically explained, then the techniques used to collect information that are presented are presented. They were observation, interview and psychometric tests. To conclude, the presentation of the results obtained during the entire investigation process is carried out, which consists of the various situations detected, the findings that contribute to the exploration and subsequently the diagnosis, which once analyzed proposes the application of a cognitive-behavioral therapeutic intervention for the treatment of depression, the conclusions, recommendations and bibliography are finally released.